Development of Hadang Ball Teaching Materials for Class X High School Students - Wajdi, Farid; Kamarudin, Azzura (Program Magister Teknologi Pendidikan Universitas Jambi, 2023)
This study investigates the impact of social media use on adolescents' mental well-being by considering the mediating role of social support and media use behavior. A cross-sectional survey method was used to collect data from 500 adolescents aged 13-18 years. The results of multiple linear regression analysis show that social media use is negatively correlated with adolescents' mental well-being. These findings indicate that adolescents who use social media with high intensity tend to experience decreased mental well-being due to lack of social support and unhealthy usage behavior. The implications of this research highlight the need for interventions that strengthen offline social support and educate adolescents about healthy social media use behaviors. The novelty of this research lies in its interdisciplinary approach which combines the perspectives of psychology, sociology and information technology to investigate complex phenomena developing in the digital era. These findings make an important contribution to our understanding of adolescent well-being in the digital era and encourage greater attention to appropriate interventions to protect the mental health of adolescents using social media.